The Lyavaraka Ultrabasic Complex, Serpentinite Belt, Kola Peninsula, Russia - Andrei Y. Barkov; Andrey A. Nikiforov; Vladimir N. Korolyuk; Robert F. Martin (Geosciences, 2022)
The Paleoproterozoic Lyavaraka ultrabasic complex is one of several dunite–harzburgite–orthopyroxenite bodies exposed as shallow plutonic complexes in the Serpentinite Belt, Kola Peninsula, Russia. Lyavaraka and the other complexes are anorogenic, formed in a stable within-plate environment in the interval 2.5–2.4 Ga as members of a large igneous province formed in the Sumian cycle of igneous activity. This geotectonic setting accounts for the shallow emplacement of the strongly magnesian komatiitic magma in the Fennoscandian Shield. We recognize three stages of crystallization of the Al-undepleted magma, present as dislocated blocks. Zone I is the ultrabasic core-like zone in which olivine predominates. Orthopyroxene is the major mineral in Zone II, and Zone III contains the most evolved ultrabasic rocks in which recurrent olivine coexists with Cpx + Pl. Primocrysts of hypermagnesian Opx (Mg# 91–93) nucleated in central areas of Zone II as olivine (Mg# 89.1–90.3) was forming in Zone I. In Zone III, olivine grains of a second generation (Mg# 74.5–75.8) formed after the primocrystic Cpx (Mg# up to 88.0) appeared. The recurrence of olivine is attributed to the progressive buildup in fO2 as a result of degassing and conversion of Fe2+ to Fe3+, well documented in our earlier studies of oxide parageneses.